Study of a new composite based on SnO2 nanoparticles — P3HT:PC71BM co-polymer blend, used as potential absorber in bulk heterojunction photovoltaic cells. (December 2022) - Radu, Alina Irina; Antohe, Vlad-Andrei; Iftimie, Sorina; Antohe, Iulia; Filipescu, Mihaela; Radu, Adrian; Coman, Diana; Stîngescu, Maria Luiza; Dinescu, Maria; Antohe, Ştefan
Abstract: The properties of a novel P3HT:PC71 BM:SnO2 -nanoparticles (NPs) composite, used as potential absorber for Organic Photovoltaic Cells (OPCs), were investigated. The structural, morphological and optical characterizations of this composite demonstrated an enhancement of the ITO/PEDOT:PSS/P3HT:PC71 BM:SnO2 -NPs/LiF/Al ternary structure when compared to the ITO/PEDOT:PSS/P3HT:PC71 BM/LiF/Al binary one. This behavior is due, on one hand to the fact that SnO2 -NPs behave as a secondary non-fullerene acceptor, and on the other hand to the superior electrical conductivity of the SnO2 -NPs, very well dispersed in the polymeric blend as compared to other nanostructured inorganic materials. These properties led to a better photogeneration and transport of charge carriers, decreasing the series resistance, increasing the fill factor, and consequently the cell's efficiency, too. The incorporation of NPs into ternary OPCs could represent a way to enhance their performances by improving the photogeneration of charge carriers, as well as their transport and collection to the electrodes. Graphical abstract: Highlights: Solar cells based on ternary P3HT:PC71 BM:SnO2 -nanoparticles compound were fabricated. SnO2 -nanoparticles addition allowed an extended absorption spectra at shorter wavelengths. EQE increased by 50% in the 400–450 nm range, when compared to the binary system. Current–voltage characteristics of the photovoltaic element revealed improved parameters.